Brain-based learning model to explore students’ procedural fluency ability in learning quadrilateral 2D shapes - Ahmad Ahmad (AMCA, 2021)
This study aims to determine the completion of student learning in procedural fluency through the Brain Based Learning model, along with their procedural fluency in flexibility, efficiency and accuracy in quadrilateral 2D shapes. It employed sequential explanatory research design. The research subjects were 7th graders (VII B) at SMP Negeri 2 Sokaraja, academic year 2019/2020. The data collection technique was procedural fluency test for students on quadrilateral 2D shapes; and the data analysis technique was the z-test. Results showed that students’ procedural fluency through BBL achieved learning mastery. In terms of flexibility, students were able to solve procedural fluency test questions in two ways. Students could perform each step of the method in terms of efficiency; and in terms of accuracy, it was shown that results were repeated consistently. These findings implied that procedural fluency through BBL along with students’ flexibility, efficiency, and accuracy belong to the fairly fluent category.